Linguistics politeness strategies in classroom interactions an exploratory mixed methods study - Umila, Karen Joy B. (2018)
This study aimed to explore the politeness strategies used by teachers in classroom interaction and the effectiveness of these strategies in learning process of students in the Ifugao context. In the qualitative phase, the linguistic aspect of politeness was transcribed and classified further using Brown and Levinson's model. Thereafter, a survey-questionnaire instrument for students was developed to determine the effectiveness of the politeness strategies in motivating, presenting lessons and discussions, managing the class, and evaluation the students. The teachers' use of positive politeness strategies was appropriate and hence effective in all the aspects of classroom interaction. However, from the perspective of the students, a combination of negative politeness, positive politeness, and bald-on record strategies was highly affective. As an output, a model for the effective use of politeness strategies in classroom interaction was developed to provide a perspective on how effective politeness strategies could be localized in the Ifugao context.
Keywords: Politeness (Linguistics); Classroom teaching strategies